Lifestyle Modification in Cardiac Patient in COVID 19 Pandemic Time - Joarder, Ariful Islam; Akand, AKM Imtiaz; Ahmed, Sharmin; Islam, Md Azharul; Mahabub, SM Ear E; Adhikary, Dipal Krishna; Haque, Md Mostashirul; Mandal, Mohammed Rayhan Masum; Khaled, Md Fakhrul Islam; Hossain, Shah Md Zakir; et al. (University Heart Journal, 2020)
Abstract not available University Heart Journal Vol. 16, No. 2, Jul 2020; 111-114